2021
DOI: 10.1017/s0022215121002103
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastic activity in chronic otitis media with cholesteatoma-related bone destruction

Abstract: Background Cholesteatoma-related bone destruction is the cause of many complications due to chronic otitis media. This study aimed to evaluate osteoclastic activity in cholesteatoma-related bone destruction using tartrate-resistant acid phosphatase 5b, an enzyme specific to osteoclastic activity. Method Seventy-two patients diagnosed with chronic otitis media were included in this study and were divided into two groups: with and without bone destruction. The blood serum and tissue tartra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Multiple studies have shown that bone destruction in cholesteatoma is mediated by the RANKL pathway. 3,4,23 Conversely, some studies have revealed potential mechanisms of bone resorption in cholesteatoma that are independent of the RANKL pathway or osteoclast activation 24,25 ; the results of the present study were consistent with those findings. Notably, estrogen plays an osteoprotective role in osteoporosis by regulating the RANKL pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have shown that bone destruction in cholesteatoma is mediated by the RANKL pathway. 3,4,23 Conversely, some studies have revealed potential mechanisms of bone resorption in cholesteatoma that are independent of the RANKL pathway or osteoclast activation 24,25 ; the results of the present study were consistent with those findings. Notably, estrogen plays an osteoprotective role in osteoporosis by regulating the RANKL pathway.…”
Section: Discussionsupporting
confidence: 92%